Design and Development of the Mobile-Based Hydroponic Planting Machine Application MyHydro - Christanto, Henoch Juli; Sutresno, Stephen Aprius; Lim, Ricardo Jonathan; Angkur, Lusiana V.G; Charmelita, Pauelina; Valentina, Vierena; Dewi, Christine (Universitas Bina Darma, 2023)
In the contemporary era, technological advancements have significantly impacted various aspects of human life, offering increased efficiency and convenience. Indonesia, aiming to enhance international competitiveness, recognizes the importance of integrating technological innovation across economic sectors. Despite its abundant natural resources, Indonesia's vital agricultural sector faces challenges, including the limited adoption of modern technology, resulting in suboptimal productivity. This study focuses on addressing these challenges by developing the MyHydro mobile application, utilizing IoT and Progressive Web App (PWA) technology to enable remote monitoring and control of hydroponic systems. The research methodology includes literature review, user requirement analysis, system design, and black-box testing. Results show that MyHydro successfully bridges the gap between traditional farming practices and modern technology. Users can efficiently monitor and control hydroponic systems, enhancing crop yields and promoting sustainability in Indonesian agriculture. In conclusion, MyHydro offers a valuable solution to modernize Indonesian farming, aligning with global trends in smart agriculture. It empowers farmers and contributes to the nation's agricultural growth.